2015
DOI: 10.1111/infa.12087
|View full text |Cite
|
Sign up to set email alerts
|

The Infant Orienting With Attention Task: Assessing the Neural Basis of Spatial Attention in Infancy

Abstract: Infant visual attention develops rapidly over the first year of life, significantly altering the way infants respond to peripheral visual events. Here we present data from 5-, 7- and 10-month-old infants using the Infant Orienting With Attention (IOWA) task, designed to capture developmental changes in visual spatial attention and saccade planning. Results indicate rapid development of spatial attention and visual response competition between 5 and 10 months. We use a dynamic neural field (DNF) model to link b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 72 publications
9
64
2
Order By: Relevance
“…Though previous work (Ross-Sheehy et al, 2015) did find significant interference effects for 10-month-old typically developing infants, the effect was smaller than for 7-month-old infants, likely reflecting increasing frontal cortical involvement at 10-months. Further, the broad age bins of the current sample may have contributed to slightly more mature profile of performance for our full-term 10-month-old infants relative to previous work (Ross-Sheehy et al, 2015). In this sample, only preterm 10-month-old infants demonstrated significant interference effects, suggesting relative deficits in the ability to quickly cancel a saccade plan, shift attention, and reorient the eyes.…”
Section: )mentioning
confidence: 67%
See 1 more Smart Citation
“…Though previous work (Ross-Sheehy et al, 2015) did find significant interference effects for 10-month-old typically developing infants, the effect was smaller than for 7-month-old infants, likely reflecting increasing frontal cortical involvement at 10-months. Further, the broad age bins of the current sample may have contributed to slightly more mature profile of performance for our full-term 10-month-old infants relative to previous work (Ross-Sheehy et al, 2015). In this sample, only preterm 10-month-old infants demonstrated significant interference effects, suggesting relative deficits in the ability to quickly cancel a saccade plan, shift attention, and reorient the eyes.…”
Section: )mentioning
confidence: 67%
“…All procedures were approved by the BLINDED Institutional Review Board (200701759). A detailed description of the methods are reported elsewhere (Ross-Sheehy, Schneegans, & Spencer, 2015), and will be summarized here.…”
Section: Stimuli Design and Proceduresmentioning
confidence: 99%
“…Six‐ and 10‐month‐olds differed marginally in the proportion of trials on which they anticipated upcoming targets, and 6‐month‐olds did look longer at the upcoming target's location (as a proportion of total looking to targets and distracters) than 10‐month‐olds did. As shown in Figure , these age‐related differences did not differ according to context; thus they are likely to reflect more general differences in the speed of eye movements and visual attention shifting between 6‐ and 10‐month‐olds (e.g., Ross‐Sheehy, Schneegans, & Spencer, ). Further, the follow‐up analysis comparing first and second trial halves showed that the difference in anticipatory dwell times between age groups was not present in the first half of the experiment, but rather emerged toward the end.…”
Section: Discussionmentioning
confidence: 84%
“…In the current study, we used a VP‐ERP procedure to examine brain–behavior relations while 4.5‐, 6‐, and 7.5‐month‐olds infants were actively engaged in the process of encoding a visual stimulus. This age range covers a major developmental transition in which the posterior orienting system reaches functional maturity, and rapid changes in the development of attention lead to gains in the volitional control of attention (e.g., Kwon, Setoodehnia, Baek, Luck, & Oakes, ; Posner & Rothbart, ; Ross‐Sheehy, Schneegans, & Spencer, ). The procedure was a combination of Fantz's () preferential looking task and Reynolds et al.…”
Section: Preferential Looking Measures Of Infant Visual Attention Andmentioning
confidence: 99%